Activation of primary sensory neurons by the topical application of capsaicin on the epidermis of a re‐innervated organotypic human skin model. Issue 1 (30th December 2013) - Lebonvallet, Nicolas; Pennec, Jean‐Pierre; Le Gall‐Ianotto, Christelle; Chéret, Jérémy; Jeanmaire, Christine; Carré, Jean‐Luc; Pauly, Gilles; Misery, Laurent
Abstract: Using an ex vivo skin‐nerve preparation, skin and nerve cells were reconstituted into a single unit and maintained in a nutrient medium bath until required experimentally. Our objective was to use the epidermis as a relay for the induction of an electric current to the neurons following the topical application of capsaicin on the skin epidermis of the skin explant, an agonist of the TRPV1 channel implicated in pruritus and pain. After 10–20 days of coculture to form the re‐innervated skin model, we applied a solution of capsaicin directly on the epidermis of the skin explant (4  μ m ). The resulting current was recorded using a path‐clamp technique on the neuronal fibres. Following the topical application of capsaicin, spontaneous activity was triggered, as characterised by repetitive spikes with periods of 125, 225 or 275 ms. This study demonstrates that the skin explant and nerve cells preparation may receive stimuli and be used to screen molecules or to study signal transmission.